PENGARUH LOKASI, PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI CAFE KUALA SEAFOOD LAMPUUK ACEH BESAR - Yaqin, Miftahul; Murad, Suryani; Pristiwa, Nara (An Nuqud Journal of Islamic Economics, 2025)
This study aims to determine the influence of Location, Promotion and Service Quality on Purchase Decisions at Cafe Kuala Seafood Lampuuk Aceh Besar. The method used is a causal method that aims to find out the influence between two or more variables in a study. The determination of the sample of this study uses the convenience sampling technique. The sample used in this study was 96 consumers at Cafe Kuala Seafood Lampuuk Aceh Besar who had purchased products and were willing to become respondents. The analysis method used is multiple linear regression analysis. The results of the study showed that location had an effect on the Purchase Decision at Cafe Kuala Seafood Lampuuk. Promotion affects the Purchase Decision at Cafe Kuala Seafood Lampuuk and the quality of service affects the Purchase Decision at Cafe Kuala Seafood Lampuuk. Location, Promotion and Quality of Service have a simultaneous effect on the Purchase Decision at Cafe Kuala Seafood Lampuuk. The quality of service has a big influence on the location and promotion on the Purchase Decision at Cafe Kuala Seafood Lampuuk Aceh Besar